Handbook of research on future policies and strategies for nation branding - Pistikou, Viktoria, 1986-; Masouras, Andreas, 1980-; Komodromos, Marcos (IGI Global, 2021)
"This book present contributed chapters that discuss the growing body of research on nation branding, beginning with an extensive overview of scholarly writing on nation branding and offering best practices as they pertain to economic dimension of the issue, cultural and social dimensions, and business dimensions"--